Studi Kasus Peran Pustakawan dalam Pengembangan Koleksi di Gedung Layanan Perpustakaan Umum Kab. Gowa - Arda, Atma; Marni, Marni; Ramadayanti, Ramadayanti (Inkunabula: Journal of Library Science and Islamic Information, 2024)
Developing library collections is crucial to meeting users' information needs. This research aims to analyze the role of librarians in collection development at the Gowa Regency Public Library. The issues raised in this research are, how is the collection development process at the Gowa Regency Public Library Service Building and what is the role of librarians in collection development at the Gowa Regency Public Library Service Building. The research method used is descriptive research with a qualitative approach. Data was collected through in-depth interviews with six librarians, observation and documentation. Data analysis and processing techniques used data reduction, data presentation and verification. The results showed that the librarians have carried out their roles in the collection development process at the library, starting from analyzing user needs, selection and procurement of collections, to collection evaluation. The obstacles faced include limited collection development budgets and lack of human resource knowledge in managing collections. The recommendations given are increasing the allocation of collection development budgets and training for librarians. Abstrak Pengembangan koleksi perpustakaan penting untuk memenuhi kebutuhan informasi pemustaka. Penelitian ini bertujuan menganalisis peran pustakawan dalam pengembangan koleksi di Perpustakaan Umum Kabupaten Gowa. Permasalahan yang diangkat dalam penelitian ini yaitu, bagaimana proses pengembangan koleksi di Gedung Layanan Perpustakaan Umum Kab. Gowa dan Bagaimana peran pustakawan dalam pengembangan koleksi di Gedung Layanan Perpustakaan Umum Kab. Gowa. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Pengumpulan data dilakukan melalui wawancara mendalam dengan enam orang pustakawan, observasi dan dokumentasi. Teknik analisis data dan pengolahan data menggunakan reduksi data, penyajian data dan verifikasi. Hasil penelitian menunjukkan bahwa pustakawan telah melaksanakan perannya dalam proses pengembangan koleksi di perpustakaan tersebut, mulai dari analisis kebutuhan pemustaka, seleksi dan pengadaan koleksi, hingga evaluasi koleksi. Kendala yang dihadapi antara lain keterbatasan anggaran pengembangan koleksi dan minimnya pengetahuan SDM dalam mengelola koleksi. Rekomendasi yang diberikan yaitu peningkatan alokasi anggaran pengembangan koleksi dan pelatihan bagi pustakawan.